Revisiting the taxonomy of Geranium kishtvariense (Geraniaceae) & notes on neotypification - Hurrah, Imtiyaz Ahmad; Wagh, Vijay Vishnu (Phytotaxa, 2021)
The confusing delineation of G. kishtvariense from its close kins is discussed here. Detailed notes on updated taxonomy, important distinguishing characters, distribution, conservation status as well as field and microscopic photographs are also provided. Additionally, a neotype for this name has also been designated here.